Improving seed production reliability of summerdormant, drought-tolerant hispanica cocksfoot - Norton M.R.; Nichols P.G.H. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Research over the last 20 years has confirmed summer-dormant, hispanica cocksfoots (Dactylis glomerata spp hispanica Roth.) to be amongst the most drought-tolerant, cool-season, perennial grasses yet commercialised. However, seed supply of this subspecies has failed to meet demand. In Australia farmers successfully grow seed of cultivars (cvv) of the related Dactylis glomerata spp glomerata and typically use similar management practises to grow hispanica cvv but usually obtain low seed yields. Research was therefore initiated to assess whether: (1) there are inherent seed production problems associated with hispanica cocksfoot and, if not: (2) focus on issues, e.g. excessively low plant density, previously identified as being possible causes of low yield. This research has demonstrated no inherent seed production limitations associated with hispanica cocksfoots. Thus, in the first trial, characterised by a dry period during reproductive growth, the cultivar Kasbah produced commercially viable yields of 450 kg/ha while in the following trial at a different location but with a similar rainfall pattern, a yield of 692 kg/ha was obtained. Another trial showed that the alleviation of moisture deficit between the stages of 75% of inflorescence emergence and 50% anthesis played an important role in maintaining seed yield and quality. These results have implications for those growers with available irrigation. On-going studies are assessing the role plant density might play in seed yield production in older swards.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)